The SKA and the MeerKAT precursor - Extreme antenna engineering - Davidson, David (2014)
© 2014 European Association on Antennas and Propagation. The Square Kilometre Array (SKA) is one of the most ambitious international mega-science projects currently in progress. This paper focusses on the antenna engineering required, looking in particular at the South African MeerKAT precursor telescope. The aperture arrays for SKA are also considered.